2011
DOI: 10.1128/jvi.05725-11
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotrophin-1 Promotes a High Survival Rate in Rabbits with Lethal Fulminant Hepatitis of Viral Origin

Abstract: Rabbit hemorrhagic disease virus (RHDV) causes lethal fulminant hepatitis closely resembling acute liver failure (ALF) in humans. In this study, we investigated whether cardiotrophin-1 (CT-1), a cytokine with hepatoprotective properties, could attenuate liver damage and prolong survival in virus-induced ALF. Twentyfour rabbits were infected with 2 ؋ 10 4 hemagglutination units of RHDV. Twelve received five doses of CT-1 (100 g/kg) starting at 12 h postinfection (hpi) (the first three doses every 6 h and then t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…However, many of the studies use one or just a few ER stressors and cell types, and thus, rapid progression to more pathophysiologically relevant animal models is essential. The RHDV, a member of the Caliciviridae family, causes in rabbits a severe form of viral hepatitis that recapitulates many of the features of human FHF and resulting in death of more than 90% of infected adult rabbits that died as result of massive liver damage within 3 days . Thus, RHDV infection constitutes a highly reproducible model of viral‐induced FHF and is of considerable interest to investigate new therapeutic avenues for this condition targeting ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, many of the studies use one or just a few ER stressors and cell types, and thus, rapid progression to more pathophysiologically relevant animal models is essential. The RHDV, a member of the Caliciviridae family, causes in rabbits a severe form of viral hepatitis that recapitulates many of the features of human FHF and resulting in death of more than 90% of infected adult rabbits that died as result of massive liver damage within 3 days . Thus, RHDV infection constitutes a highly reproducible model of viral‐induced FHF and is of considerable interest to investigate new therapeutic avenues for this condition targeting ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that CT-1 deficient mice are susceptible to ischemia/reperfusion liver injury and other pro-apoptotic insults indicates that CT-1 acts as a natural defense of the liver against damage. Consistently, it has been shown that administration of rCT-1 affords protection against ischemia/ reperfusion liver damage [93], galactosamine [96] and hepatitis of viral origin [95]. An adenovirus encoding CT-1 protected rats against fulminant hepatitis induced by massive hepatic resection [91].…”
Section: Livermentioning
confidence: 95%
“…Soon after its discovery, CT-1 was shown to be a potent inducer of the acute phase response in rat primary hepatocytes [2,90] and subsequent studies showed that CT-1 is an essential factor in the defense of the liver against a variety of insults [91][92][93][94][95]. In the liver CT-1 mRNA is expressed by both hepatocytes and non-parenchymal cells [94].…”
Section: Livermentioning
confidence: 97%
“…Rabbit Sirc cells used in this study have been described previously [13]. A549 cells were a kind gift from Heinrich Hoffmann (Microbiology Department, Icahn School of Medicine at Mount Sinai), HapT1 were a kind gift from Rubén Hernández-Alcoceba (CIMA, Universidad de Navarra), WHC17 were a kind gift from Dr. Michael Roggendorf (Center for Biomedical Biotechnology-Universitat Duisburg Essen), Huh7.0 cells expressing HCV genome were generated as described previously [14].…”
Section: Methodsmentioning
confidence: 99%